Management of Librarian to Supporting Lecturer's Performance in Higher Education - Rahmadanita, Annisa; Hasmiati, Hasmiati (Department Library of Governance Institut of Home Affairs, 2020)
Problem Statement: The author focuses on the problem of limited human resources of IPDN libraries. Purpose: This study is focused on knowing the description of IPDN library human resource management in supporting the performance of lecturers in the IPDN environment. Method: The author collects data through interviews, observation, documentation. Result: The results showed that from the aspect of planning and organizing, there was an inadequate number of human resources, as well as the quality of human resources that needed to be improved in the IPDN Library. Conclusion: Library human resource management in supporting the performance of lecturers at IPDN has been carried out quite well, but IPDN Libraries need to make improvements and improvements from the aspects of planning and organizing, namely by adding personnel and developing human resources. Keywords: Management; Librarian; Human Resource; Lecturer's Performance; Higher Education